Financial services distribution - Devlin, James (Henry Stewart Talks, 2008)
Distribution in financial services: roles fulfilled, Direct distribution channels, Bank assurance, Indirect distribution channels, Technology driven channels, Current issues: the retail distribution review and the Thoresen review of generic financial advice